2015
DOI: 10.1016/j.jecp.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring age differences in visual working memory capacity: Is there a contribution of memory for configuration?

Abstract: Recent research has shown marked developmental increases in the apparent capacity of working memory. This recent research is based largely on performance on tasks in which a visual array is to be retained briefly for comparison with a subsequent probe display. Here we examine a possible theoretical alternative (or supplement) to a developmental increase in working memory, in which children could improve in the ability to combine items in an array to form a coherent configuration. Elementary school children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 54 publications
5
31
0
1
Order By: Relevance
“…We anticipate that the age invariance of contextual and metacognitive benefits would ultimately break down beyond the age range examined here. Different relationships are likely to hold, for example, during childhood, when VSTM performance is improving ( Burnett Heyes, Zokaei, van der Staaij, Bays, & Husain, 2012 ; Cowan et al, 2006 ; Gathercole, Pickering, Ambridge, & Wearing, 2004 ; Sarigiannidis, Crickmore, & Astle, 2016 ), and use of configural context has recently been shown to differ from adults ( Cowan, Saults, & Clark, 2015 ). Performance is also expected to depend on different neural constraints during development and senescence ( Sander, Lindenberger, & Werkle-Bergner, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that the age invariance of contextual and metacognitive benefits would ultimately break down beyond the age range examined here. Different relationships are likely to hold, for example, during childhood, when VSTM performance is improving ( Burnett Heyes, Zokaei, van der Staaij, Bays, & Husain, 2012 ; Cowan et al, 2006 ; Gathercole, Pickering, Ambridge, & Wearing, 2004 ; Sarigiannidis, Crickmore, & Astle, 2016 ), and use of configural context has recently been shown to differ from adults ( Cowan, Saults, & Clark, 2015 ). Performance is also expected to depend on different neural constraints during development and senescence ( Sander, Lindenberger, & Werkle-Bergner, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that the age invariance of contextual and metacognitive benefits would ultimately break down beyond the age range examined here. Different relationships are likely to hold, for example, during childhood, when VSTM performance is improving (Gathercole et al, 2004;Cowan et al, 2006;Burnett Heyes et al, 2012;Sarigiannidis et al, 2016), and use of configural context has recently been shown to differ from adults (Cowan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Adults hold fewer details within an item (e.g., pattern of lines filling a shape) in WM relative to the item shape (e.g., oval or rectangle) (Fukuda et al, 2010). Developmentally, VWM performance typically improves between childhood and adulthood (e.g., Cowan et al, 2006;Cowan, Saults, et al, 2015). This performance improvement is thought to reflect an increase in WM capacity across childhood (Riggs et al, 2006;Simmering, 2012) and into adulthood (Cowan et al, 2010;Cowan, Ricker, et al, 2015).…”
Section: Atypical Development Of Visual Working Memory Performance In Autism Spectrum Disordermentioning
confidence: 99%